2012
DOI: 10.3390/s120303472
|View full text |Cite
|
Sign up to set email alerts
|

N-Acyl Homoserine Lactone Production by Klebsiella pneumoniae Isolated from Human Tongue Surface

Abstract: Bacteria communicate by producing quorum sensing molecules called autoinducers, which include autoinducer-1, an N-hexanoyl homoserine lactone (AHL), and autoinducer-2. Bacteria present in the human oral cavity have been shown to produce autoinducer-2, but not AHL. Here, we report the isolation of two AHL-producing Klebsiella pneumoniae strains from the posterior dorsal surface of the tongue of a healthy individual. Spent culture supernatant extracts from K. pneumoniae activated the biosensors Agrobacterium tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…Upon screening K. pneumoniae, (KF817575) showed consistent induction of violacein production in reporter strain indicating its ability to produce AHL. Results obtained in this study is comparable with those of Yin et al [29] who reported the production of both short and long chain AHLs in K. pneumoniae. Limitations were there in screening the spoilage microflora for their signal molecule production as C. violaceum CECT5999 responds only to short range of AHLs [30].…”
Section: Discussionsupporting
confidence: 95%
“…Upon screening K. pneumoniae, (KF817575) showed consistent induction of violacein production in reporter strain indicating its ability to produce AHL. Results obtained in this study is comparable with those of Yin et al [29] who reported the production of both short and long chain AHLs in K. pneumoniae. Limitations were there in screening the spoilage microflora for their signal molecule production as C. violaceum CECT5999 responds only to short range of AHLs [30].…”
Section: Discussionsupporting
confidence: 95%
“…Recently, we have isolated two AHL-producing K. pneumoniae strains from the posterior dorsal surface of the tongue of a healthy individual [17]. Here we report the isolation of Enterobacter sp.…”
Section: Introductionmentioning
confidence: 84%
“…Mass spectrometry parameters and mobile phases used were essentially performed according to a reported method [20]. Precursor ion-scanning analysis were performed in positive ion mode with Q3 set to monitor for m / z 102 and Q1 set to scan a mass range of m / z 80 to 400.…”
Section: Methodsmentioning
confidence: 99%